Recovery method, electrode manufacturing method and recovery system
By employing a two-step treatment with an aromatic hydrocarbon compound and water, the method effectively separates and recovers electrode active materials, addressing inefficiencies in existing separation methods and preserving the electrode's structural integrity.
Patent Information
- Application Number
- JP2023008046
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-01-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-01-23
AI Technical Summary
Existing methods for separating and recovering active material powder from electrodes are not sufficiently efficient, necessitating a more effective process for easy separation and recovery.
A method involving a first treatment liquid with an aromatic hydrocarbon compound in a reduced state and metal ions, followed by a second treatment with water, is used to separate the electrode active material from the binder, promoting carbonization and reducing binding properties to facilitate easy recovery.
The method allows for efficient separation and recovery of electrode active materials while minimizing damage to the crystal structure, enabling the reuse of electrodes and reducing processing time and aromatic hydrocarbon compound usage.
Smart Images

Figure 0007605232000013 
Figure 0007605232000014 
Figure 0007605232000015
Abstract
Description
[Technical field]
[0001] Disclosed herein are a recovery method, a method for manufacturing an electrode, and a recovery system. [Background technology]
[0002] Conventionally, methods have been proposed for recycling electrodes by recovering the active material powder from the electrodes, subjecting them to different regeneration treatments, either hydrothermal treatment with short annealing or solid-state synthesis, and turning the regenerated electrode material into a slurry for use in the manufacture of new batteries (e.g., Non-Patent Document 1). [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Green Chem.,2018,20,851-862 Summary of the Invention [Problem to be solved by the invention]
[0004] However, separation and recovery of active material powder from electrodes has not been fully investigated, and there has been a demand for an easier method of separating and recovering active material from electrodes.
[0005] The present disclosure has been made in consideration of such problems, and has as its main object to provide a novel recovery method, electrode manufacturing method, and recovery system that can more easily separate and recover active material from an electrode. [Means for solving the problem]
[0006] As a result of intensive research to achieve the above-mentioned object, the inventors have found that the active material can be more easily separated and recovered by contacting an electrode with a specified first treatment liquid and a second treatment liquid containing water, and have thus completed the present disclosure.
[0007] That is, the recovery method disclosed in the present specification is as follows: A method for recovering an electrode active material from a treatment target electrode including an electrode mixture containing an electrode active material and a binder, comprising: a separation step of contacting the electrode to be treated with a first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and a metal ion and a second treatment liquid containing water, and separating the electrode active material from the electrode to be treated; It is something.
[0008] The method for producing an electrode according to the present disclosure includes: An electrode preparation step of preparing a new electrode using the electrode active material recovered by the above-mentioned recovery method, It is something.
[0009] The recovery system of the present disclosure comprises: A recovery system for recovering an electrode active material from a treatment target electrode including an electrode mixture containing an electrode active material and a binder, a separation unit that carries out a separation process in which a first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and a metal ion and a second treatment liquid containing water are brought into contact with the electrode to be treated, and the electrode active material is separated from the electrode to be treated; It is something. Effect of the Invention
[0010] In the recovery method, electrode manufacturing method, and recovery system of the present disclosure, the active material can be more easily separated and recovered from the electrode. The reason why such an effect is obtained is presumed to be as follows. For example, the first treatment liquid containing a reduced aromatic hydrocarbon compound and metal ions donates electrons to a binder such as a fluorine-containing polymer, thereby promoting carbonization of the binder and at the same time reducing the binding property. Furthermore, the second treatment liquid containing water promotes the reaction that reduces the binding property. This makes it possible to easily separate and recover the electrode active material from the electrode to be treated. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is an explanatory diagram showing an example of a recovery system 50 and a separation process. [Diagram 2]FIG. 2 is an explanatory diagram showing an example of the state of the processing target electrode 10 during separation processing. [Diagram 3] Reaction equation for the reduction of binders, etc. by Li-Naph. [Figure 4] Reaction equation for Li-Naph with water. [Diagram 5] XRD patterns of powders obtained in the separation steps of Experimental Examples 1 to 6. [Figure 6] XRD patterns of powders obtained in the separation steps of Experimental Examples 7 to 10. [Figure 7] XRD patterns of powders obtained in the separation steps of Experimental Examples 11 to 16. [Figure 8] XRD patterns of powders obtained in the separation steps of Experimental Examples 17 to 22. [Figure 9] XRD patterns of powders obtained in the separation steps of Experimental Examples 45 to 50. [Figure 10] XRD pattern of the powder obtained in the separation process of Experimental Example 51. [Figure 11] Peak of the 003 plane of LiNi1 / 3Co1 / 3Mn1 / 3O2 in the XRD patterns of the powders obtained in the separation steps of Experimental Examples 1 to 22. [Figure 12] Peak of the 111 plane of LiFePO4 in the XRD pattern of the powder obtained in the separation process of Experimental Examples 45 to 50. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The recovery method, electrode manufacturing method, and recovery system of the present disclosure relate to electrodes for power storage devices. Examples of power storage devices include hybrid capacitors, pseudo electric double layer capacitors, alkali metal secondary batteries such as lithium and sodium, alkali metal ion batteries, and air batteries. Metal ions as carrier ions include, for example, alkali metal ions such as Li, Na, K, and Group 2 ions (alkaline earth metal ions) such as Mg, Ca, Sr, etc., among which lithium ions are preferred. Among these, as the power storage device, a lithium secondary battery, particularly a lithium ion secondary battery, is preferred. Here, it will be mainly described assuming that the power storage device is a lithium secondary battery. The power storage device may include, for example, a positive electrode having a positive electrode active material that occludes and releases lithium ions, a negative electrode having a negative electrode active material that occludes and releases lithium ions, and an electrolytic solution that is interposed between the positive electrode and the negative electrode and conducts lithium ions. This power storage device may include a separator between the positive electrode and the negative electrode.
[0013] The positive electrode may include a positive electrode composite material containing a positive electrode active material and a binder. The positive electrode composite material may be formed on the surface of the current collector. The positive electrode composite material may include, in addition to the positive electrode active material and the binder, a conductive material, etc. The positive electrode is, for example, a mixture of a positive electrode active material, a binder, and, if necessary, a conductive material, with an appropriate solvent added to form a paste-like positive electrode composite material, which is applied and dried on the surface of the current collector, and compressed if necessary to increase the electrode density for formation. Examples of the positive electrode active material include compounds containing lithium and transition metal elements, and oxides containing lithium and transition metal elements are preferred. The positive electrode active material has, for example, a basic composition formula of Li (1-x) MnO2 (0 < x < 1, etc., the same below), Li (1-x) Mn2O4 and other lithium manganese composite oxides, a basic composition formula of Li (1-x) CoO2 and other lithium cobalt composite oxides, a basic composition formula of Li (1-x) NiO2 and other lithium nickel composite oxides, a basic composition formula of Li (1-x) Ni a Co b Mn cLithium nickel cobalt manganese composite oxide such as O2 (a+b+c=1) can be used. Alternatively, the positive electrode active material may be lithium iron phosphate. The "basic composition formula" means that other elements may be included.
[0014] The binder plays a role of binding the active material particles and the conductive material particles, and may be, for example, a fluorine-containing resin such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), or fluorine rubber, or a thermoplastic resin such as polypropylene or polyethylene, ethylene propylene diene monomer (EPDM) rubber, sulfonated EPDM rubber, or natural butyl rubber (NBR), either alone or as a mixture of two or more of them. In addition, aqueous binders such as cellulose-based carboxymethyl cellulose (CMC), styrene butadiene copolymer (SBR), and aqueous dispersions of polyvinyl alcohol, etc., may also be used.
[0015] The conductive material is not particularly limited as long as it is an electron conductive material that does not adversely affect the battery performance, and for example, graphite such as natural graphite (scale graphite, flake graphite) and artificial graphite, carbon materials such as acetylene black, carbon black, ketjen black, carbon whisker, needle coke, and carbon fiber, and metals (copper, nickel, aluminum, silver, gold, etc.) can be used alone or in a mixture of two or more. As a solvent for dispersing the positive electrode active material, conductive material, and binder, for example, organic solvents such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethylenetriamine, N,N-dimethylaminopropylamine, ethylene oxide, and tetrahydrofuran can be used. In addition, a dispersant, a thickener, etc. can be added to water, and the active material can be slurried with latex such as SBR. As a thickener, for example, polysaccharides such as carboxymethylcellulose and methylcellulose can be used alone or as a mixture of two or more. Examples of the application method include roller coating such as an applicator roll, screen coating, doctor blade method, spin coating, bar coater, and the like, and any thickness and shape can be obtained by using any of these. Examples of the current collector include aluminum, titanium, stainless steel, nickel, iron, baked carbon, conductive polymer, conductive glass, and the like, as well as aluminum or copper whose surface is treated with carbon, nickel, titanium, silver, and the like for the purpose of improving adhesion, conductivity, and oxidation resistance. The surfaces of these can also be subjected to oxidation treatment. Examples of the shape of the current collector include foil, film, sheet, net, punched or expanded, lath, porous, foamed, and fiber group formed bodies. The thickness of the current collector is, for example, 1 to 500 μm.
[0016] The negative electrode may include a negative electrode mixture containing a negative electrode active material and a binder. The negative electrode mixture may be formed on the surface of a current collector. The negative electrode mixture may include a conductive material in addition to the negative electrode active material and the binder. The negative electrode may be formed by, for example, mixing a negative electrode active material, a binder, and optionally a conductive material, adding an appropriate solvent to form a paste-like negative electrode mixture, applying it to the surface of a current collector, drying it, and compressing it to increase the electrode density as necessary. Examples of the negative electrode active material include inorganic compounds such as lithium, lithium alloys, and tin compounds, carbon materials capable of absorbing and releasing lithium ions, composite oxides containing multiple elements, and conductive polymers. Examples of the carbon material include cokes, glassy carbons, graphites, non-graphitizable carbons, pyrolytic carbons, and carbon fibers. Examples of the composite oxide include lithium titanium composite oxide and lithium vanadium composite oxide. As the binder, conductive material, solvent, coating method, and current collector for the negative electrode, one or more of those exemplified for the positive electrode can be used.
[0017] The electrolyte may be, for example, an electrolyte in which a supporting salt is dissolved. Examples of the supporting salt include lithium salts such as LiPF6 and LiBF4. Examples of the solvent for the electrolyte include carbonates, esters, ethers, nitriles, furans, sulfolanes, and dioxolanes, which may be used alone or in combination. Specifically, examples of the carbonate include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), butylene carbonate, and chloroethylene carbonate, and chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate, ethyl-n-butyl carbonate, methyl-t-butyl carbonate, di-i-propyl carbonate, and t-butyl-i-propyl carbonate. The electrolyte may be a solid ion-conductive polymer, an inorganic solid electrolyte, a mixed material of an organic polymer electrolyte and an inorganic solid electrolyte, or an inorganic solid powder bound by an organic binder.
[0018] [Collection method] The recovery method of the present disclosure is a method for recovering an electrode active material from a target electrode having an electrode mixture containing an electrode active material and a binder. This recovery method includes a separation step of contacting the target electrode with a first treatment liquid and a second treatment liquid, and separating the electrode active material from the target electrode. This electrode treatment method may be performed under conditions that suppress destruction of the crystal structure of the electrode active material before and after the separation step.
[0019] (Electrode to be treated) The electrode to be treated may be either the positive or negative electrode of the above-mentioned power storage device, but is preferably the positive electrode. The electrode to be treated is preferably an oxide containing the same type of metal ion as the metal ion contained in the first treatment liquid described later, and is preferably a lithium transition metal composite oxide, and more preferably a composite oxide containing lithium, nickel, manganese, and cobalt, or a composite oxide containing lithium and iron. The binder contained in the electrode to be treated preferably contains a fluorine-containing polymer (fluorine-containing resin) such as polyvinylidene fluoride. The electrode to be treated may be a new product such as a scrap material left over from the electrode manufacturing process, or may be a used product. In this electrode to be treated, the electrode active material is preferably in a state in which it can occlude and release carrier ions, and is preferably not deactivated.
[0020] (Processing solution) The first treatment liquid includes an aromatic hydrocarbon compound in a reduced state and metal ions. The first treatment liquid may include an aromatic hydrocarbon compound represented by one or more of the following formulas (1) and (2). The first treatment liquid may be obtained by one or more of the following formulas (3) and (4). That is, the first treatment liquid may include an aromatic hydrocarbon compound in a reduced state and metal ions by reacting a metal with an aromatic hydrocarbon compound. The metal is preferably one that is highly reactive to react with an aromatic hydrocarbon compound, and is preferably an alkali metal or a metal of Group 2 element. The first treatment liquid may include an aromatic hydrocarbon compound represented by one or more of naphthalene, biphenyl, ortho-terphenyl, anthracene, and para-terphenyl. As the aromatic hydrocarbon compound, naphthalene and biphenyl are preferable. The first treatment liquid may include a metal ion represented by one or more of lithium ions, sodium ions, and potassium ions. Of these metal ions, lithium ions are more preferable.
[0021] The first treatment liquid may contain a first solvent which is an ether-based compound. The first solvent may be, for example, a cyclic ether-based compound or a chain ether-based compound. The first solvent may be one or more of tetrahydrofuran (THF), dioxolane (DOL), dioxane (DOX), diethyl ether (DEE), dimethoxyethane (DME), diglyme (G2), triglyme (G3), and tetraglyme (G4). Among these, DME and THF are more preferable, and DME is even more preferable. The first treatment liquid is preferably one in which the first solvent is DME and Li metal is reacted with any one of naphthalene, biphenyl, and ortho-terphenyl, as shown in the formulas (5) to (7). When such a first treatment liquid is used, the electrode active material is easily separated from the electrode, and at that time, destruction of the crystal structure of the electrode active material is also suppressed.
[0022] In this first treatment liquid, the concentration of the aromatic hydrocarbon compound in a reduced state relative to the entire first treatment liquid may be 0.05 mol / L or more, 0.1 mol / L or more, 0.15 mol / L or more, or 0.20 mol / L or more from the viewpoint of more reliably separating the electrode active material from the electrode to be treated. Moreover, this concentration may be 2 mol / L or less, 1 mol / L or less, or 0.5 mol / L or less from the viewpoint of reducing the amount of the aromatic hydrocarbon compound in a reduced state used and from the viewpoint of suppressing destruction of the crystal structure of the electrode active material.
[0023] [ka]
[0024] [ka]
[0025] [ka]
[0026] The first treatment liquid is considered to have a function of promoting carbonization of the binder and at the same time reducing the binding property by donating electrons to the binder. The first treatment liquid may have a function of restoring the capacity of the electrode to be treated, the capacity of which has been deteriorated, by donating electrons and carrier ions to the electrode active material.
[0027] This first treatment liquid may contain a solvent used in the electrolyte of the power storage device as the second solvent. Examples of the second solvent include those exemplified as the solvent of the electrolyte in the above-mentioned power storage device. It is presumed that the first treatment liquid shows either a brown liquid or a dark green liquid, and the reducing power changes depending on whether or not it contains the second solvent. The less the second solvent is contained, the higher the reducing power is, and the more the second solvent is contained, the milder the reducing power is. Therefore, whether or not to add the second solvent and the amount of the second solvent to be added may be appropriately determined according to the desired reducing power.
[0028] The second treatment liquid may contain water, but preferably contains more water. The second treatment liquid may contain, for example, 50% by mass or more of water, 80% by mass or more of water, or 90% by mass or more of water. The second treatment liquid may be water.
[0029] (separation process) In the separation step, a separation process is performed in which the first treatment liquid and the second treatment liquid are brought into contact with the electrode to be treated. In the separation step, for example, a first process in which the first treatment liquid is brought into contact with the electrode to be treated, and a second process in which the second treatment liquid is brought into contact with the electrode to be treated may be performed. In the separation step, the second treatment liquid may be brought into contact with the electrode to be treated while the first treatment liquid is in contact with the electrode to be treated. In the following, a case will be mainly described in which the first treatment liquid is brought into contact with the electrode to be treated by the first treatment, and then the second treatment liquid is brought into contact with the electrode to be treated by the second treatment.
[0030] In the first treatment, the electrode to be treated is brought into contact with the first treatment liquid. It is considered that the binding strength of the binder of the electrode to be treated is reduced by such a first treatment. The method of bringing the electrode to be treated into contact with the first treatment liquid is not particularly limited, and may be, for example, a method of immersing the electrode to be treated in the first treatment liquid, or a method of applying the first treatment liquid to the electrode to be treated by spraying or dropping. In the first treatment, the electrode to be treated may be immersed in the first treatment liquid and stirred. The treatment time for the first treatment is not particularly limited, but may be, for example, 10 seconds or more, 1 minute or more, 2 minutes or more, or 5 minutes or more from the viewpoint of spreading the first treatment liquid to the binder inside the electrode to be treated. In addition, the treatment time for the first treatment may be, for example, 1 hour or less, 30 minutes or less, 20 minutes or less, or 15 minutes or less from the viewpoint of shortening the treatment time and suppressing destruction of the crystal structure of the electrode active material. In addition, this treatment time may be the immersion time when the first treatment is immersion. The treatment time may be the time from when the electrode to be treated comes into contact with the first treatment liquid until when it comes into contact with the second treatment liquid. In the first treatment, the amount of the first treatment liquid used is not particularly limited, but from the viewpoint of spreading the first treatment liquid to the binder inside the electrode to be treated, it may be, for example, 0.1 times or more of the mass of the electrode mixture, 0.2 times or more, or 0.5 times or more. In addition, from the viewpoint of reducing the amount of aromatic hydrocarbon compounds used, the amount of the first treatment liquid used may be, for example, 10 times or less of the mass of the electrode mixture, 5 times or less, or 3 times or less. In the first treatment, it is preferable to use a first treatment liquid having a concentration of aromatic hydrocarbon compounds in a reduced state of 0.5 mol / L or less. The lower the concentration of aromatic hydrocarbon compounds in a reduced state, the milder the reducing power of the first treatment liquid, and the more the destruction of the crystal structure of the electrode active material can be suppressed. The treatment temperature when the first treatment is performed is not particularly limited, and may be, for example, in the range of 10° C. to 60° C., or in the range of 20° C. to 40° C. The treatment temperature is preferably near room temperature (20° C. to 25° C.). In this first treatment, unnecessary first treatment liquid may be removed from the treatment target electrode or the powder containing the electrode active material after the first treatment, for example, by filtering the used first treatment liquid.
[0031] In the second treatment, the second treatment liquid is brought into contact with the electrode to be treated that has been in contact with the first treatment liquid by the first treatment. It is believed that the binding strength of the binder of the electrode to be treated is further reduced by such a second treatment. The method of bringing the electrode to be treated into contact with the second treatment liquid is not particularly limited, and may be, for example, a method of immersing the electrode to be treated in the second treatment liquid, or a method of applying the second treatment liquid to the electrode to be treated by spraying or dropping. In the second treatment, the electrode to be treated may be immersed in the second treatment liquid and stirred. The treatment time for performing the second treatment is not particularly limited, but may be, for example, 10 seconds or more, 1 minute or more, or 2 minutes or more from the viewpoint of spreading the second treatment liquid to the binder inside the electrode to be treated. In addition, the treatment time when performing the second treatment may be, for example, 1 hour or less, 30 minutes or less, 15 minutes or less, or 5 minutes or less from the viewpoint of shortening the treatment time. In addition, when the second treatment is immersion, this treatment time may be the immersion time. The treatment time may be the time from when the electrode to be treated comes into contact with the second treatment liquid until removal of the second treatment liquid is started. In the second treatment, the amount of the second treatment liquid used is not particularly limited, but may be, for example, 0.1 times or more, 0.2 times or more, or 0.5 times or more of the mass of the electrode mixture from the viewpoint of spreading the second treatment liquid to the binder inside the electrode to be treated. In addition, the amount of the second treatment liquid used may be, for example, 10 times or less, 5 times or less, or 3 times or less of the mass of the electrode mixture. The treatment temperature when the second treatment is performed is not particularly limited, but may be, for example, in the range of 10°C to 60°C, or in the range of 20°C to 40°C. The treatment temperature is preferably near room temperature (20°C to 25°C). In this second treatment, unnecessary second treatment liquid may be removed from the electrode to be treated after the second treatment or the powder containing the electrode active material by filtering the used second treatment liquid.
[0032] In this separation step, after the first and second treatments, solvent washing may be performed to wash at least one of the electrode to be treated and the powder containing the electrode active material with a washing solution containing a solvent capable of dissolving aromatic hydrocarbon compounds. By such solvent washing, aromatic hydrocarbon compounds and the like resulting from the first treatment solution are removed. Examples of the solvent capable of dissolving aromatic hydrocarbon compounds include the above-mentioned ether-based compounds. The solvent used in the washing solution may be the same as or different from the ether-based compound contained in the first treatment solution.
[0033] In this separation step, after the first and second treatments, water washing may be performed to wash at least one of the electrode to be treated and the powder containing the electrode active material with washing water containing water. It is considered that such water washing can remove metal ions and the like resulting from the first treatment liquid.
[0034] In this separation step, the electrode active material can be separated from the electrode to be treated by simply contacting the electrode to be treated, which includes an electrode mixture containing an electrode active material and a binder, with a first treatment liquid containing a reduced aromatic hydrocarbon compound and metal ions, and a second treatment liquid containing water. For example, as shown in Figs. 1 and 2, when a first treatment is performed in which the electrode to be treated 10 is brought into contact with the first treatment liquid 20, a reaction as shown in Fig. 3A proceeds, and the binding strength of the binder contained in the positive electrode mixture 14 decreases. Furthermore, when a second treatment is performed in which the electrode to be treated 10 in contact with the first treatment liquid 20 is brought into contact with the second treatment liquid 25, a reaction as shown in Fig. 4 proceeds, and the decrease in the binding strength of the binder contained in the positive electrode mixture 14 is promoted. As a result, the electrode to be treated 10 is decomposed into a current collector 12, an electrode active material 16, and a mixture member 18. The mixture member 18 contains components of a conductive material and a binder other than the positive electrode active material. Thus, in this separation step, the electrode active material can be separated from the electrode to be treated. Depending on the conditions of the first treatment, the electrode to be treated 10 may be decomposed into the current collector 12, the electrode active material 16, and the composite member 18 by the first treatment alone. However, by carrying out the second treatment, the electrode to be treated 10 can be decomposed into the current collector 12, the electrode active material 16, and the composite member 18 even if the first treatment is carried out under milder conditions. This allows the amount of aromatic hydrocarbon compound used and the treatment time to be reduced, and the electrode active material can be efficiently separated from the electrode to be treated. In addition, carrying out the first treatment under milder conditions is preferable because destruction of the crystal structure of the electrode active material 16 by the first treatment is further suppressed.
[0035] In this separation step, the capacity of the electrode to be treated, which has been degraded, may be restored. For example, when the above-mentioned first treatment is performed on the electrode 10 to be treated, which has been degraded in capacity, in addition to the reaction shown in FIG. 3A, the reaction shown in FIG. 3B proceeds, and the charge / discharge activity of the positive electrode active material is restored. By utilizing this, the electrode active material can be separated from the electrode to be treated in the separation step, and the capacity of the electrode active material can be restored at the same time.
[0036] In this recovery method, for example, the deterioration degree of the electrode to be treated is determined, and depending on the result, the electrode active material may be separated from the electrode to be treated and recovered, or may be recovered as an electrode without being separated. For example, when the electrode is deteriorated to such an extent that it cannot be reused in the state of an electrode, the electrode active material separated from the electrode to be treated by the above-mentioned separation step is recovered, and when the electrode is deteriorated to such an extent that it can be reused in the state of an electrode, the capacity may be restored by the first process among the above-mentioned separation steps, the second process may be omitted, and the electrode active material with the restored capacity may be recovered without being separated from the electrode to be treated. In this way, the electrode active material can be recovered in a more appropriate state according to the deterioration degree of the electrode to be treated. The deterioration degree of the electrode to be treated may be determined, for example, using the power storage device before the electrode to be treated is taken out, and may be defined, for example, as the ratio of the capacity after deterioration to the initial capacity, or may be estimated based on the AC impedance.
[0037] In the XRD pattern obtained by X-ray diffraction (XRD) measurement of the electrode active material recovered by this recovery method, the peak intensity I at 2θ where the peak intensity is the maximum intensity I0 when measuring an unused electrode active material is preferably 0.2 times or more of the maximum intensity I0. This peak intensity I is preferably 0.5 times or more, more preferably 0.7 times or more, of the maximum intensity I0. This peak intensity I is considered to be I0 or less, but the larger the value, the more the destruction of the crystal structure of the active material is suppressed, which is preferable. For example, the peak with the maximum intensity I0 is when the electrode active material is LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 In the case of O2, it may be the peak of the 003 plane (2θ=18.7°), and in the case of the electrode active material LiFePO4, it may be the peak of the 111 plane (2θ=25.6°).
[0038] [Electrode manufacturing method] The electrode manufacturing method of the present disclosure includes an electrode manufacturing step of manufacturing a new electrode using the electrode active material separated from the electrode to be treated by the above-mentioned electrode treatment method. In the electrode manufacturing step, the electrode active material may be mixed with a binder and / or a conductive material, if necessary, to obtain an electrode mixture, which may be applied to a current collector to manufacture the electrode. In this electrode manufacturing method, one or more of the binder, conductive material, solvent, application method, and current collector exemplified for the positive electrode may be used.
[0039] [Collection system] The recovery system of the present disclosure is a recovery system that recovers an electrode active material from a target electrode having an electrode mixture containing an electrode active material and a binder. This recovery system includes a separation unit that brings a first treatment liquid and a second treatment liquid into contact with the target electrode and performs a separation process to separate the electrode active material from the target electrode. The recovery system 50 in FIG. 1 is an example of this recovery system and includes a separation unit 30.
[0040] The separation unit 30 is a facility or device that separates the electrode active material 16 from the electrode 10 to be treated. In this separation unit 30, the first treatment liquid 20 and the second treatment liquid 25 are brought into contact with the electrode 10 to be treated, and the electrode active material 16 is separated from the electrode 10 to be treated. In the recovery system 50, the separation unit 30 is configured to bring the first treatment liquid 20 into contact with the electrode 10 to be treated by the first treatment, and then bring the second treatment liquid 25 into contact with the electrode 10 to be treated by the second treatment, and separate the electrode active material 16 from the electrode 10 to be treated. In the separation unit 30, for example, the treatment described in the above-mentioned separation step may be performed.
[0041] The recovery system 50 may include, for example, a control unit (not shown) that controls the entire recovery system 50. The recovery system may also include a determination unit (not shown) that determines the deterioration degree of the electrode to be treated. In the recovery system 50, the control unit may, for example, control the determination unit to determine the deterioration degree of the electrode to be treated 10, and control the separation unit 30 according to the result to switch between separating and recovering the electrode active material 16 from the electrode to be treated 10, or recovering the electrode as it is without separating it. The determination unit may be configured to make a determination using the power storage device before the electrode to be treated 10 is taken out, and may be configured to determine the deterioration degree based on the capacity, or may be configured to estimate the deterioration degree based on the AC impedance.
[0042] In the recovery method, electrode manufacturing method, and recovery system of the present embodiment described above, the active material can be more easily separated and recovered from the electrode. The reason why such an effect is obtained is presumed to be as follows. For example, the first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and metal ions donates electrons to a binder such as a fluorine-containing polymer, thereby promoting carbonization of the binder and at the same time reducing the binding property. Furthermore, the second treatment liquid containing water promotes the reaction that reduces the binding property. This makes it possible to easily separate and recover the electrode active material from the electrode to be treated. Note that, depending on the conditions of the first treatment, the electrode active material may be separated from the electrode to be treated only by the first treatment, but by performing the second treatment, the electrode active material can be separated from the electrode to be treated even if the first treatment is performed under milder conditions. This allows the amount of aromatic hydrocarbon compound used and the treatment time to be reduced, and the electrode active material can be efficiently separated and recovered from the electrode to be treated. In addition, performing the first treatment under milder conditions is preferable because the destruction of the crystal structure of the active material by the first treatment is more suppressed.
[0043] It is to be noted that the present disclosure is not limited to the above-described embodiment, and can be embodied in various forms as long as it falls within the technical scope of the present disclosure. For example, in the above-described embodiment, when a used product is used as the electrode to be treated, an introduction step of introducing metal ions to be carrier ions into the electrode active material may be performed before the separation step, after the separation step, after the electrode preparation step, or the like.
[0044] The present disclosure may be any one of the following [1] to
[10] . [1] A method for recovering an electrode active material from a treatment target electrode having an electrode mixture containing an electrode active material and a binder, comprising: a separation step of contacting the electrode to be treated with a first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and a metal ion and a second treatment liquid containing water, and separating the electrode active material from the electrode to be treated; Recovery method. [2] The recovery method according to [1], in the separation step, the second treatment liquid is brought into contact with the electrode to be treated while the first treatment liquid is in contact with the electrode to be treated. [3] The method according to [1] or [2], wherein the first treatment liquid has a concentration of the reduced aromatic hydrocarbon compounds of 0.1 mol / L or more and 0.5 mol / L or less in the separation step. [4] The recovery method according to any one of [1] to [3], wherein in the separation step, the electrode to be treated is contacted with the first treatment liquid for a contact time of 1 minute or more and 20 minutes or less. [5] The method according to any one of [1] to [4], wherein the binder contains a fluorine-containing polymer. [6] The method according to any one of [1] to [5], wherein the electrode active material is an oxide containing the metal ion. [7] The method for recovering an aromatic hydrocarbon compound according to any one of [1] to [6], wherein the aromatic hydrocarbon compound is one or more of the compounds represented by formulae (1) to (2). [C1] TIFF0007605232000004.tif35141[8] The method according to any one of [1] to [7], wherein the first processing liquid contains one or more of dimethoxyethane (DME), tetrahydrofuran (THF), diethyl ether (DEE), diglyme (G2), triglyme (G3), and tetraglyme (G4). [9] An electrode preparation step of preparing a new electrode using the electrode active material recovered by the recovery method according to any one of [1] to [8]. A method for manufacturing an electrode.
[10] A recovery system for recovering an electrode active material from a treatment target electrode comprising an electrode mixture containing an electrode active material and a binder, a separation unit that carries out a separation process in which a first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and a metal ion and a second treatment liquid containing water are brought into contact with the electrode to be treated, and the electrode active material is separated from the electrode to be treated; Collection system. EXAMPLES
[0045] Examples in which the electrode treatment method of the present disclosure was specifically examined are described below as Experimental Examples, in which Experimental Examples 1 to 22 and 45 to 53 correspond to Examples of the present disclosure, and Experimental Examples 23 to 44 correspond to Reference Examples.
[0046] [Experimental Examples 1-6] (Electrode to be treated) LiNi as a positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode composite material containing 92% by mass of O2 (NCM, Toda Kogyo Co., Ltd.), 5% by mass of acetylene black (Denka Co., Ltd.) as a conductive material, and 3% by mass of polyvinylidene fluoride (Kureha Co., Ltd.) as a binder was used with a weight of 7 mg / cm. 2 An electrode was prepared by forming the above-mentioned on one side of an aluminum current collecting foil, and this was used as the treatment target electrode.
[0047] (Processing solution) In an inert atmosphere, naphthalene was dissolved in 1,2-dimethoxyethane (DME) solvent to a concentration of 1.00 mol / L, and then lithium metal was added to the solvent to achieve the same concentration as that of naphthalene, and the mixture was stirred. A dark green anion radical liquid composition with a lithium naphthalenide (Li-Naph) concentration of 1.00 mol / L was prepared by the reaction shown in the above formula (5). The prepared anion radical liquid composition was used as the first treatment liquid. Water was used as the second treatment liquid.
[0048] (separation process) The electrode to be treated was placed at a distance of 20 cm for 10 mL (approximately 10 g) of the first treatment solution. 2 The electrode mixture was then immersed in the solution and stirred for 5 minutes in Experimental Example 1, 10 minutes in Experimental Example 2, 15 minutes in Experimental Example 3, 30 minutes in Experimental Example 4, 45 minutes in Experimental Example 5, and 60 minutes in Experimental Example 6 (first treatment). After that, the first treatment solution and the electrode mixture peeled off from the electrode to be treated were transferred from the container to a funnel, and suction filtration was performed using a vacuum pump. Next, the electrode to be treated was washed with water by pouring water into the container in which the electrode to be treated remained and stirring the mixture (second treatment). After that, the water and the electrode mixture peeled off from the electrode to be treated were transferred from the container to the previous funnel and suction filtration was performed. Then, the same water washing as before and solvent washing using THF instead of water were alternately repeated. The water washing after the second treatment was performed for the purpose of removing remaining lithium ions, and the solvent washing was performed for the purpose of removing remaining naphthalene. In this way, the electrode to be treated (current collector foil) from which the electrode mixture was peeled off and the powder (electrode active material) separated from the electrode to be treated were obtained.
[0049] (Evaluation of peeling state) The treated electrodes from which the electrode mixture had peeled off were visually inspected and the percentage of the area from which the electrode mixture had peeled off was roughly evaluated. The results are shown in Table 1. The evaluation was carried out as follows: "A" if the electrode mixture had been almost completely peeled off, "B" if about 50% of the electrode mixture had been peeled off, and "C" if about 20% had been peeled off.
[0050] (Evaluation of crystal state) The obtained powder was dried in a vacuum at 120°C, and then X-ray diffraction (XRD) was performed using an X-ray diffraction measuring device (Ultima IV, Rigaku) to confirm the crystal structure. In the XRD measurement, CuKα (wavelength 1.54051 Å) was used, and the applied voltage was 40 kV, the current was 30 mA, the sampling width was 0.020° / min, and the scan speed was 5° min. -1 The measurements were performed at angles ranging from 15° to 50° (2θ) with a 350 nm XRD. The crystal state was evaluated based on the obtained XRD patterns. The results are shown in Table 1. 1 / 3 Co 1 / 3 Mn 1 / 3 When the peak of the 003 plane of O2 (2θ = 18.7°) is present, it is judged that the destruction of the crystal structure is suppressed and is rated as "A". 1 / 3 Co 1 / 3 Mn 1 / 3 When there was no peak of the 003 plane of O2, it was judged that the crystal structure was destroyed and was marked as "B". 1 / 3 Co 1 / 3 Mn 1 / 3 The peak intensity of the 003 plane of O2 was normalized to 1.00, and when the intensity of the corresponding peak of the powder of each experimental example was 0.2 or more, it was judged that a peak was present, and when it was less than 0.2, a peak was judged to be absent.
[0051] [Experimental Examples 7-22] Except for changing the Li-Naph concentration in the first treatment liquid from 1.00 mol / L to 0.50 mol / L, Experimental Examples 7 to 10 were performed in the same manner as Experimental Examples 1, 2, 5, and 6. Also, except for changing the Li-Naph concentration in the first treatment liquid to 0.25 mol / L, Experimental Examples 11 to 16 were performed in the same manner as Experimental Examples 1 to 6. Also, except for changing the Li-Naph concentration in the first treatment liquid to 0.10 mol / L, Experimental Examples 17 to 22 were performed in the same manner as Experimental Examples 1 to 6.
[0052] [Experimental Examples 23-44] Experimental Examples 23 to 44 were carried out in the same manner as Experimental Examples 1 to 22, except that in the separation step, after the first treatment, the second treatment and water washing were omitted, and solvent washing using THF was carried out.
[0053] [Experimental Examples 45-50] The positive electrode active material of the electrode to be treated is LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Except for changing O2 to LiFePO4, Experimental Examples 45 to 50 were carried out in the same manner as Experimental Examples 1 to 6. The crystal state was evaluated as follows: when there was a peak (2θ=25.6°) of the 111 plane of LiFePO4, it was judged that the destruction of the crystal structure was suppressed, and it was rated as "A", and when there was no peak of the 111 plane of LiFePO4, it was judged that the crystal structure was destroyed, and it was rated as "B". At that time, the intensity of the peak of the 111 plane of unused LiFePO4 was normalized as 1.00, and when the intensity of the corresponding peak of the powder of each experimental example was 0.2 or more, it was judged that there was a peak, and when it was less than 0.2, it was judged that there was no peak.
[0054] [Experimental Examples 51-53] The solvent of the first treatment liquid was changed from DME to tetrahydrofuran (THF). Moreover, instead of immersing the electrode to be treated in the first treatment liquid in the first treatment, 160 mg of the first treatment liquid was sprayed onto the electrode to be treated. Thereafter, a second treatment was performed in which the electrode to be treated after the spray treatment was immersed in water for 1 minute so that the entire electrode was immersed. Other than these, Experimental Example 51 was performed in the same manner as Experimental Example 1. Moreover, Experimental Example 52 was performed in the same manner as Experimental Example 51, except that the amount of the first treatment liquid sprayed was changed from 160 mg to 110 mg. Moreover, Experimental Example 53 was performed in the same manner as Experimental Example 51, except that the amount of the first treatment liquid sprayed was changed from 160 mg to 46 mg. Moreover, when a 20 cm electrode to be treated was sprayed, 2 The mass of the positive electrode active material contained in the positive electrode mixture was 70 mg, and the mass of the positive electrode mixture was 76.1 mg. The ratio of the spray amount of the first treatment liquid to the mass of the positive electrode mixture was 2.1 in Experimental Example 51, 1.4 in Experimental Example 52, and 0.6 in Experimental Example 53.
[0055] [Results and Discussion] Tables 1 to 4 summarize the active material, first treatment, second treatment, peeling state, and crystal state for Experimental Examples 1 to 22, 23 to 44, 45 to 50, and 51 to 53. Table 5 summarizes the influence of the presence or absence of the second treatment, the Li-Naph concentration of the first treatment liquid, and the treatment time of the first treatment on the peeling state for Experimental Examples 1 to 44. Table 6 summarizes the influence of the Li-Naph concentration of the first treatment liquid and the treatment time of the first treatment on the crystal state for Experimental Examples 1 to 22. Table 7 summarizes the influence of the Li-Naph concentration of the first treatment liquid and the treatment time of the first treatment on the crystal state for Experimental Examples 45 to 50. Figures 5 to 10 show the XRD patterns of the powders obtained in the separation process for Experimental Examples 1 to 6, 7 to 10, 11 to 16, 17 to 22, 45 to 50, and 51. Figure 11 shows the XRD patterns of LiNi in the XRD patterns of the powders obtained in the separation process for Experimental Examples 1 to 22. 1 / 3 Co 1 / 3 Mn 1 / 3 12 shows the peak of the 111 plane of LiFePO4 in the XRD patterns of the powders obtained in the separation steps of Experimental Examples 45 to 50.
[0056] As shown in Tables 1, 2, and 5, in Experimental Examples 1 to 44, in Experimental Examples 23 to 44 in which the second treatment was not performed, the electrode mixture was completely peeled off when the first treatment liquid with a Li-Naph concentration of 1.00 mol / L was used, but when the first treatment liquid with a Li-Naph concentration of 0.50 mol / L was used, only about 50% of the electrode mixture was peeled off, and when the first treatment liquid with a Li-Naph concentration of 0.25 mol / L or less was used, only about 20% of the electrode mixture was peeled off. On the other hand, in Experimental Examples 1 to 22 in which the second treatment was performed, it was found that the electrode mixture was completely peeled off, and the electrode active material could be more easily separated from the electrode to be treated. From this, it was found that the electrode active material could be more easily separated by performing the second treatment. However, in Experimental Examples 17 to 22 in which the Li-Naph concentration was 0.1 mol / L, the electrode mixture was peeled off as flakes rather than powder, so it was inferred that when it is necessary to separate the electrode active material from the composite material and recover it, the Li-Naph concentration is preferably more than 0.1 mol / L.
[0057] As shown in Table 3, in Experimental Examples 45 to 50 in which the second treatment was performed, the positive electrode active material was LiFePO4, but in all cases the electrode mixture was completely peeled off. From this, it was found that the type of positive electrode active material is not particularly limited. Also, as shown in Table 4, in Experimental Examples 51 to 53 in which the second treatment was performed, the first treatment was performed by spraying instead of immersion, but in all cases the electrode mixture was completely peeled off. From this, it was found that the method of contacting the electrode to be treated with the first treatment liquid is not particularly limited. Similarly, it was inferred that the method of contacting the electrode to be treated with the second treatment liquid is not particularly limited.
[0058] As shown in Tables 1, 2, 6, and 7, it was found that the lower the Li-Naph concentration in the first treatment solution and the shorter the treatment time of the first treatment, the less likely the crystal structure is to be destroyed, and the more suitable it is for recycling, which is preferable. From this viewpoint, it was found that the Li-Naph concentration is preferably, for example, 0.5 mol / L or less. It was also found that the treatment time of the first treatment is preferably 20 minutes or less.
[0059] [Table 1]
[0060] [Table 2]
[0061] [Table 3]
[0062] [Table 4]
[0063] [Table 5]
[0064] [Table 6]
[0065] [Table 7]
[0066] It goes without saying that the present disclosure is in no way limited to the above-described embodiments, and can be embodied in various forms as long as they fall within the technical scope of the present disclosure. [Industrial Applicability]
[0067] The present disclosure is applicable to the technical field of electricity storage devices. [Explanation of symbols]
[0068] 10 electrode to be treated, 12 current collector, 14 positive electrode composite, 16 electrode active material, 18 composite member, 20 first treatment liquid, 25 second treatment liquid, 30 separation section, 50 recovery system.
Claims
1. A method for recovering an electrode active material from a treatment target electrode including an electrode mixture containing an electrode active material and a binder, comprising: a separation step of contacting the electrode to be treated with a first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and a metal ion and a second treatment liquid containing water, and separating the electrode active material from the electrode to be treated; Recovery method.
2. The recovery method according to claim 1 , wherein in the separating step, the second treatment liquid is brought into contact with the electrode to be treated while the first treatment liquid is in contact with the electrode to be treated.
3. 3. The method according to claim 1, wherein the first processing liquid has a concentration of the reduced aromatic hydrocarbon compounds of 0.1 mol / L or more and 0.5 mol / L or less in the separation step.
4. 3. The recovery method according to claim 1, wherein in the separation step, a contact time for contacting the electrode to be treated with the first treatment liquid is set to be 1 minute or more and 20 minutes or less.
5. The recovery method according to claim 1 , wherein the binder comprises a fluorine-containing polymer.
6. The method according to claim 1 or 2, wherein the electrode active material is an oxide containing the metal ions.
7. The method for recovering aromatic hydrocarbon compounds according to claim 1 or 2, wherein the aromatic hydrocarbon compounds are one or more of the compounds represented by formulas (1) to (2). 【Chemistry 1】
8. 3. The method according to claim 1, wherein the first processing liquid contains one or more of dimethoxyethane (DME), tetrahydrofuran (THF), diethyl ether (DEE), diglyme (G2), triglyme (G3), and tetraglyme (G4).
9. The electrode active material recovered by the recovery method according to claim 1 or 2 includes a step of producing a new electrode using the electrode active material recovered by the recovery method according to claim 1 or 2. A method for manufacturing an electrode.
10. A recovery system for recovering an electrode active material from a treatment target electrode including an electrode mixture containing an electrode active material and a binder, a separation unit that carries out a separation process in which a first treatment liquid containing an aromatic hydrocarbon compound in a reduced state and a metal ion and a second treatment liquid containing water are brought into contact with the electrode to be treated, and the electrode active material is separated from the electrode to be treated; Collection system.
Citation Information
Patent Citations
Remover for secondary battery electrode material and method of processing secondary battery using the same
JP2008204755A
Method for recovering active material from discarded battery material
JP2012186150A
Lithium recovery method
WO2013114621A1
